Development of a Ball Return Device for Free Throw Practice in Basketball - Christo Kesaulya; Priyanto Priyanto; Moch. Senoadji Karjadi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This research developed a modified PVC-based ball return device to optimize self-directed free throw practice in basketball. Using the Research and Devel-opment (RnD) method, product feasibility was evaluated through expert valida-tion a dual scale user trail involving Sports Coaching Education students. The expert validation yielded an overall score 540 points (90%), categorizing the de-vice as highly feasible. Structurally, the design and construction aspect scored 86%, while functional capability and safety-durability achieved 91% and 94%, respectively. Empirical testing demonstrated significant quality improvement, with small-scale scores rising consistently across all aspect to reach 80% (de-sign), 82% (function), 83% (safety) in the large-scale trial. Validator suggested adding front netting to catch erratic rebounds and guide a higher parabolic shooting arc. In conclusion, this affordable, portable, tool is highly viable for accelerating shooting repetition and athlete’s performance.